DAMPAK ERA DIGITAL TERHADAP PERLINDUNGAN KONSUMEN DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH - Riski, Darlin (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The era of the digital economy has brought about a major transformation in the way transactions are conducted, which provides convenience but also poses various risks such as fraud and privacy violations. This study aims to investigate the impact of digitalization on consumer protection in the context of sharia economic law, which emphasizes fairness and transparency. Using the literature review method, this study examines relevant literature to draw reflective and in-depth conclusions. The results of the study show that digitalization brings convenience in transactions but also significant risks that many contradict sharia principles. Consumers are often not adequately protected in digital transactions, which can lead to fraud and privacy violations, violating the principles of transparency and fairness. The findings emphasized the need to improve regulation and supervision of digital transactions as well as increase consumer awareness to ensure fair and transparent transactions, in line with sharia principles. The research underscores the importance of consumer education and stronger regulation to ensure consumer protection in the digital age. Furthermore, business actors must integrate sharia principles in their practices to support fair and transparent trade.